GE_GERICHTE C/3715/2018 vom 11. Januar 2019 - GE Cour de justice (2019)
MAINLEVÉE PROVISOIRE ; RECONNAISSANCE DE DETTE ; RÉQUISITION DE POURSUITE ; CÉDULE HYPOTHÉCAIRE ; GAGE ; DÉNONCIATION(EN GÉNÉRAL) | CPC.180.al1; LP.82.al1; LP.67.al1.ch1; LP.67.al1.ch2; LP.67.al2; LP.151.al1.leta; CC.794.al1; CC.818.al1.ch1; CC.847.al1